THE IMPLEMENTATION OF EDUCATION MANAGEMENT ON MI NU MIFTAHUL HUDA 01 KUDUS FULL DAY SCHOOL PROGRAM - Anni Qurrotul Aini; Husni Mubarok; Muhammad Khoirul Anam; Murtafi'ah Murtafi'ah; Dina Sakhiratul Rizki; Nadiya Ruhma; Rizka Lu’lu’atul Afroh; Syukriyah Barokah (FASHLUNA, 2022)
This study aims to determine how the planning and implementation of the full day program as the implementation of educational management at MI NU Miftahul Huda 01 Kudus. In this study used a qualitative descriptive method. Subject study is teacher’s and student’s in MI NU Miftahul Huda 01 Kudus. Data collection methods used interview, observation, and documentation. Qualitative data analysis techniques used interactive data analysis techniques. The results of the study stated that the learning planning in the full day school program at MI NU Mitahul Huda 01 Kudus is not much different from the regular school learning plan, the difference only lies in the implementation of learning activities that require more time allocation than all processes that will be carried out as the process of determining, preparing various decisions on the implementation of learning that will be carried out in the future to achieve learning objectives and the use of available educational resources in an integrated manner. Full day school implementation at MI NU Miftahul Huda 01 Kudus is carried out effectively after teaching and learning activities are completed. The full day school program is carried out evenly covering grades 1 to 6 with students who are interested in attending full day school.